2016
DOI: 10.1016/j.nmd.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone reduces respiratory complications in patients with Duchenne muscular dystrophy

Abstract: In Duchenne muscular dystrophy (DMD), progressive loss of respiratory function leads to restrictive pulmonary disease and places patients at significant risk for severe respiratory complications. Of particular concern are ineffective cough, secretion retention and recurrent respiratory tract infections. In a Phase 3 randomized controlled study (DMD Long-term Idebenone Study, DELOS) in DMD patients 10-18 years of age and not taking concomitant glucocorticoid steroids, idebenone (900 mg/day) reduced significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…In a phase II clinical trial, Idebenone showed positive effects on functional cardiac and respiratory parameters in DMD patients [52]. A phase III clinical trial showed reduction of loss of respiratory functions in DMD patients, even in the absence of glucocorticoid treatment [53,54].…”
Section: Alternative Approachesmentioning
confidence: 99%
“…In a phase II clinical trial, Idebenone showed positive effects on functional cardiac and respiratory parameters in DMD patients [52]. A phase III clinical trial showed reduction of loss of respiratory functions in DMD patients, even in the absence of glucocorticoid treatment [53,54].…”
Section: Alternative Approachesmentioning
confidence: 99%
“…This gap has been fixed by the introduction of a different molecule: idebenone, a short-chain benzoquinone characterized by potent antioxidant activity and with the ability to stimulate mitochondrial electron flux and cellular energy production [16,17]. It has been shown in multicenter clinical trials that idebenone is able to slow the decline of pulmonary function of DMD patients, with a consequent reduced risk of bronchopulmonary complications and a reduced need for systemic antibiotics [6,7,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, loss of respiratory function continues to be a predominant cause of early morbidity and mortality in DMD patients [6]. Therefore, prevention of these complications and institution of early treatment as necessary now represent major goals [7]. To this end, tools able to stratify patients on the basis of their risk to develop respiratory complications would be a landmark improvement in the management of DMD.…”
Section: -21 10%mentioning
confidence: 99%
“…We have identified 19 studies fulfilling our selection criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ( Figure 1): nine studies exploring the effect of steroids on pulmonary function, [17][18][19][20][21][22][23][24][25] six studies exploring the effect of idebenone (one study explored the effect of both steroids and idebenone), 19,[26][27][28][29][30] three studies about eteplirsen, [31][32][33] one study about ataluren, 34 and one study about stem-cell therapy 35 (Tables 1-3).…”
Section: Therapeutic Agents Investigatedmentioning
confidence: 99%